Jejak Penyebaran Agama Islam Oleh Syekh Al Hajj Ngali Hasyim: Mursyid Thoriqoh Lampung Tengah - Ratnawati, Dewi; Karsiwan (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
The spread of Islam in the Central Lampung region, especially in Sidomulyo Village, cannot be separated from the charismatic figure known as Sheikh Al Hajj Ngali Hasyim. He is a thoriqoh murshid who is known in many areas such as Central Lampung, West Lampung, South Lampung, North Sumatra, South Sumatra, East Aceh and also Palembang. This article is a qualitative study with a historical approach, researching and investigating all aspects of Sheikh Al Hajj Ngali Hasyim's life, starting from his biography, his role, his preaching methods, to the traces of the spread of Islam in Central Lampung. Interviews, observation and documentation were used as data collection techniques. The aim of this research is to understand how Sheikh Al Hajj Ngali Hasyim tried to spread Islam in the region and what da'wah methods he used to spread Islam. The research results show that Sheikh Al Hajj Ngali Hasyim used three methods in spreading Islam, namely 1) business or trade methods, 2) thoriqoh methods and 3) educational methods. Among his activities he also preached at several special mosques using the mauidha hasanah method. Sheikh Al Hajj Ngali Hasyim is committed to making this area a religious village, so he strives to realize his ideals by always inviting people to believe